Land Policies and Evolving Farm Structures in Transition Countries - Lerman, Zvi; Csaki, Csaba; Feder, Gershon (World Bank, Washington, DC, 2013)
The authors review the role of land policies in the evolving farm structure of transition countries in Central and Eastern Europe (CEE) and the Commonwealth of Independent States (CIS). They show how different policies for land property rights, degrees of control of land rental and sale markets, and procedures for restructuring former collective or state farms resulted in significantly different farm structures in CEE countries compared with those in the CIS. In particular, secure land rights, greater emphasis on indivualization of land, and more liberal land market policies in CEE generated a farming sector with a relatively large share of family farms and viable corporate farms. On the other hand, limited tenure security, ineffective individualization of land rights, and restrictive land policies in most of the CIS produced a farming structure dominated by large and generally nonviable jointly-owned farms that function much like the old collective farms. Family farms are slow to emerge in transition countries with inadequate land policies. The agricultural sector in countries dominated by inefficient farm organizations is characterized by low productivity and misallocation of resources.